Factors affecting the sales reduction for SLT 4G LTE product in SLT mobitel Trincomalee branch - Jasitharan, M.; Kumaradeepan, V. (South Eastern University of Sri Lanka, 2024)
The organization success and the failures depend on the number of sales that achieved by the organization per month. This article is about the research investigate about the factors behind the sales reduction of 4G LTE product in SLT Mobitel Trincomalee branch. The research was conducted among the customers across the Trincomalee region. Researcher has identified Product quality, Price, Brand competition, Promotion, Customer relationship as the independent variable. A mixed-method approach was employed, incorporating both primary and secondary data collection methods. Primary data were gathered through surveys and depth interviews with a sample of 451 customers, selected using simple random sampling from a population of 4,500. Secondary data, including sales reports and disconnection data, were also analyzed. For the data analysis part, the researcher has used SPSS tool. The study concludes that SLT Mobitel must enhance service quality, reconsider pricing strategies, and increase promotional efforts to regain market share and improve future sales performance. The insights gained from this research provide actionable recommendations for SLT Mobitel to better align with customer expectations and enhance their competitive position in the telecommunications industry.
Keywords: Sales reduction; Sales; SLT Mobitel; Telecommunication; Trincomalee